PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI TOKO AREI OUTDOOR GEAR CABANG SINTANG - Magdalena, Lin (Universitas Kapuas Sintang, 2024)
The aim of this research is to determine the influence of product quality on customer satisfaction at the Arei Outdoor Gear Shop, Sintang Branch. Type of quantitative research with a population of customers who shop at the Arei Outdoor Gear Shop, Sintang Branch. The number of samples was 96 respondents. There are two research variables, namely the independent variable X (Product Quality) and the dependent variable Y (Customer Satisfaction). The data collection instrument is a questionnaire, measured using a Likert scale. Data collection techniques use questionnaires, observation and documentation. The data analysis technique uses quantitative data analysis. Data analysis: validity test, reliability test and hypothesis test consisting of simple linear regression test, correlation test (r), t test, coefficient of determination test (R²). Research results: all variables tested obtained valid results. The instrument used is reliable because the Cronbach Alpha value for variable X is 0.940 > 0.6 and the Cronbach Alpha for variable Y is 0.813 > 0.6. Simple linear regression test with the equation Y = 5.075 + 0.488. The constant b is the regression coefficient number which has a value of 0.488. The correlation test for variables X and Y has a very strong relationship with a correlation result of 0.909. T test results with calculated value 21,182 > ᵗtable 1.985. So H0 is rejected and Ha is accepted. The R test result is 0.827, meaning that variable X influences variable Y by 82.7%, while 17.3% is influenced by other variables.